2013
DOI: 10.1093/imrn/rnt015
|View full text |Cite
|
Sign up to set email alerts
|

On Fourier Analytic Properties of Graphs

Abstract: We study the Fourier dimensions of graphs of real-valued functions defined on the unit interval [0, 1]. Our results imply that the graph of fractional Brownian motion is almost surely not a Salem set, answering in part a question of Kahane from 1993, and that the graph of a Baire typical function in C[0, 1] has Fourier dimension zero.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…In 1993, Kahane [16] outlined the problem explicitly. Kahane's problem for graphs, even in the case of the standard Brownian motion W t , however, remained open for quite a while until, together with T. Orponen, we established that the Brownian graph G(W ) is almost surely not a Salem set [9]. It turned out that the reason for this is purely geometric: the proof was based on the following application of a Fourier-analytic version of Marstrand's slicing lemma.…”
Section: Introduction and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1993, Kahane [16] outlined the problem explicitly. Kahane's problem for graphs, even in the case of the standard Brownian motion W t , however, remained open for quite a while until, together with T. Orponen, we established that the Brownian graph G(W ) is almost surely not a Salem set [9]. It turned out that the reason for this is purely geometric: the proof was based on the following application of a Fourier-analytic version of Marstrand's slicing lemma.…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…The methods in [9] are purely geometric and involve no stochastic properties of Brownian motion. They also do not shed any light on the precise value for the Fourier dimension of G(W ).…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…For d = 1, the middle-thirds Cantor set in R has Fourier dimension 0 and Hausdorff dimension ln 2/ ln 3. Some subtle properties of Fourier dimension are studied by Ekström, Persson, and Schmeling [16] and Fraser, Orponen, and Sahlsten [19].…”
Section: 1)mentioning
confidence: 99%
“…Fraser et al found in [FOS3] another interesting application for this inequality: they showed that any one-dimensional graph has Fourier dimension 1. More precisely, in general dimensions Theorem 8.5 For any function f : A → R n−m , A ⊂ R m , and for its graph…”
Section: Slicing Theoremsmentioning
confidence: 99%